Tunable Release of Calcium from Chitosan-Coated Bioglass - Vuk Uskoković; Gabriel Abuna; Joseph Ryan Hampton; Saulo Geraldeli (MDPI AG, 2023)
Bioglass presents a standard biomaterial for regeneration of hard tissues in orthopedics and dentistry. The notable osteo-inductive properties of bioglass are largely due to the release of calcium ions from it. However, this release is not easily controllable and can often be excessive, especially during the initial interaction of the biomaterial with the surrounding tissues. Consequently, this excessive release can deplete the calcium content of the bioglass, ultimately reducing its overall bioactivity. In this study, we have tested if applying biopolymer chitosan coatings of different thicknesses would be able to mitigate and regulate the calcium ion release from monodisperse bioglass nanoparticles. Calcium release was assessed for four different chitosan coating thicknesses at different time points over the period of 28 days using a fluorescence quencher. Expectedly, chitosan-coated particles released less calcium as the concentration of chitosan in the coating solution increased, presumably due to the increased thickness of the chitosan coating around the bioglass particles. The mechanism of release remained constant for each coating thickness, corresponding to anomalous, non-Fickian diffusion, but the degree of anomalousness increased with the deposition of chitosan. Zeta potential testing showed an expected increase in the positive double layer charge following the deposition of the chitosan coating due to the surface exposure of the amine groups of chitosan. Less intuitively, the zeta potential became less positive as thickness of the chitosan coating increased, attesting to the lower density of the surface charges within thicker coatings than within the thinner ones. Overall, the findings of this study demonstrate that chitosan coating efficiently prevents the early release of calcium from bioglass. This coating procedure also allows for the tuning of the calcium release kinetics by controlling the chitosan concentration in the parent solution.